A Portugal with a crown or a Phrygian cap? Spanish Perspectives of a Monarquia do Norte (1919) - Comesaña, Alfredo (Cuadernos de Historia Contemporánea, 2022)
In 1919 the last great monarchical revolt broke out against the Portuguese Republic, an event known as the Monarchy of the North. The goal of this study is to analyze its polyhedral impact on Spanish public opinion, which, looking at itself in the Portuguese mirror, debated what was the ideal regime, republic or monarchy, and what should be the bases of understanding that would normalize Spanish-Portuguese relations, hitherto marked by reciprocal mistrust. On the other hand, the protection provided by politicians and the Spanish republican press to the Portuguese Republic is also addressed, denouncing the support that the Portuguese monarchism received in Spain.